Time Divested or Time Invested? Freshmen’s Perspectives and Reflective Experiences on Interactive School Learning - Simon Adjei Tachie; Israel Kariyana (Research in Social Sciences and Technology, 2022)
This study sought to research first-year South African university students’ attitudes towards interactive school learning and then to determine their perspectives and reflective experiences regarding interactive learning. Data was gathered during the first week of their first university lectures. The sample was 129 freshmen. The study adopted a mixed-method approach that utilized a sequential explanatory research design. Data was gathered through questionnaires and interviews. Quantitative data was coded and analysed through descriptive statistics using SPSS version 23, while qualitative data was thematically analysed through content analysis. Permission to conduct the study was granted by the lecturers and the participants. It emerged from the study that, though participants were positive about the provision of interactive school learning, their school experiences told different stories about such activities. Participants valued interactive school learning as it improves learners’ socialization experiences, communication skills, and thinking skills. Interactive school learning also promotes teamwork and personal engagement, which are necessary to improve the quality of education. The study concluded that, while interactive school learning added value to education, most schools did not offer such opportunities to enhance learning experiences. The study recommends that schools offer school-based opportunities and teaching practices that accommodate learners’ varied learning styles across all subjects.